Generalisation of A-equitable preference in multiobjective optimisation problems. (2nd September 2021) - Foroutannia, D.; Merati, M.
Abstract : The concept of A -equitable efficiency in solving the multiobjective optimisation problems have recently been introduced by Mut and Wiecek [Generalised equitable preference in multiobjective programming. Euro J Oper Res. 2011;212:535–551], where A is an arbitrary matrix with non-negative entries. The preference relation of this concept solution, ⪯ e ( A ), does not satisfy the strict monotonicity and strict principle of transfers axioms in general, therefore the set of A -equitably efficient solutions is not contained within the set of equitably efficient solutions and the set of Pareto-optimal solutions for the same problem. In this paper, we extend the work done by Mut and Wiecek and state the new conditions on the matrix A that guarantee to satisfy these axioms by the preference relation ⪯ e ( A ) . The other contribution of this paper is the use of the preference relation ⪯ e ( Δ A ) to solve the multio objective optimisation problems instead of ⪯ e ( A ) . This has the advantage that the decision-maker has more freedom to choose the preferences matrix A . The relation ⪯ e ( Δ A ) has become an equitable rational preference relation by imposing the weaker conditions on entries of A, in comparison to the relation ⪯ e ( A ) .